Influence of cork on the physical, thermal and mechanical properties of the concrete block - Farfán Córdova, Marlon Gastón (2024)
This research intends to determine the influence of granulated cork on the physical, thermal and mechanical properties of the concrete block. Absorption, density, moisture content, compressive strength and thermal conductivity tests were carried out on concrete blocks produced in a traditional way, with a substitution of sand by granulated cork at 3 % and 5 % in two experimental groups, in addition to one standard group. In the case of the physical properties, absorption presented average values of 9.47 %, 8.23 %, and 9.37 % for the standard group (BP) and experimental groups (BC3 and BC5) respectively. Density values showed an increase as the percentage of cork grew, reaching a density of 2088.77 kg/m3 for the group with 5 % cork. Respecting moisture content, its values decreased from 13.67 % for BP, 11.87 % for BC3, and finally 9.23 % for BC5. The mechanical property of compressive strength showed variations of increase and decrease with values of 19.53 kg/cm2 for the BP group, 23.10 kg/cm2 for the BC3 group, and 16.21 kg/cm2 for the BC5 group. Lastly, for the thermal conductivity test, the results decreased as expected with values of 0.387 W/mK, 0.3164 W/mK, and 0.3036 W/mK for the BP, BC3 and BC5 groups respectively. These data processed with statistical tests showed that the incorporation of granulated cork in the concrete block has a significant influence on its physical, thermal and mechanical properties.